Preparation method of high-purity hydroxyapatite dry powder

By utilizing particle size differences to separate hydroxyapatite and impurity crystalline phase particles in a spray dryer, the problem of difficult removal of metastable crystalline phases in existing technologies has been solved, enabling the preparation of high-purity hydroxyapatite dry powder and reducing energy consumption.

CN121180960APending Publication Date: 2025-12-23JIAXING LIMEI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511251422.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-03
Publication Date
2025-12-23

AI Technical Summary

Technical Problem

In the preparation of hydroxyapatite, existing technologies struggle to remove metastable crystalline phases, resulting in limited purity improvement and high energy consumption. There is a lack of energy-efficient purification and drying methods.

Method used

A precursor solution is formed by mixing a hydroxyapatite precursor containing impurity crystalline phases with water. The solution is then ground and dispersed into a slurry in a ball mill. The slurry is then crushed by high-pressure airflow in a spray dryer. The hydroxyapatite and impurity crystalline phase particles are separated by the difference in particle size, forming agglomerates of different particle sizes. The impurities are then separated by gravity and adsorption to obtain high-purity hydroxyapatite dry powder.

Benefits of technology

This method achieves the removal of impurity phases and drying without altering the crystal structure, resulting in high-purity hydroxyapatite powder that is easy to store and use, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121180960A_ABST
    Figure CN121180960A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-purity hydroxyapatite dry powder. The preparation method comprises the following steps: mixing a hydroxyapatite precursor containing an impurity crystal phase with water to form a precursor solution; putting the precursor solution into a ball mill, grinding and dispersing to form slurry, putting the ground and dispersed slurry into a spray dryer, and crushing the slurry into hydroxyapatite particles and impurity crystal phase particles under the action of high-pressure airflow of the spray dryer; the hydroxyapatite particles and the impurity crystal phase particles are agglomerated in the falling process to form hydroxyapatite agglomerates and impurity crystal phase agglomerates with different particle sizes, and due to different particle sizes, the hydroxyapatite agglomerates and the impurity crystal phase agglomerates are separated, so that the high-purity hydroxyapatite dry powder is prepared; according to the method, impurity crystal phases can be removed, the product can be dried, and the high-purity hydroxyapatite dry powder is obtained and is convenient to store and apply.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic materials technology, and in particular to a method for preparing high-purity hydroxyapatite dry powder. Background Technology

[0002] Hydroxyapatite (HAP) is a natural or synthetic calcium phosphate mineral with the chemical formula Ca. 10 (PO4)6(OH)2, with a molecular weight of 1004.62. Hydroxyapatite is an important inorganic component of vertebrate bones and teeth, possessing good biocompatibility and bioactivity, and is widely used in biomedicine, environmental remediation, catalysis, sensors, and other fields.

[0003] In existing technologies, hydroxyapatite can be mass-produced via precipitation. However, during the solution crystallization process, the high concentrations of calcium and phosphate ions in these methods lead to the formation of metastable crystalline phases such as calcium hydrogen phosphate dihydrate (DCPD) and octacalcium phosphate, which are difficult to remove by washing. The mainstream strategy is to control the crystallization process, such as increasing the reaction temperature, extending the reaction time, or using additives, to prevent the formation of impurity phases like DCPD, or to rapidly convert these phases into hydroxyapatite once they have formed. However, these purification processes only control the crystallization process, resulting in a solution containing hydroxyapatite, which is inconvenient for storage and application, requiring additional high-temperature drying or sintering steps.

[0004] Sintering requires evaporating the solvent at temperatures above 400°C to obtain dry powder. During sintering, the metastable crystalline phase decomposes or undergoes a solid-state phase transformation, thus transforming into hydroxyapatite. However, because hydroxyapatite (Ca... 10 The chemical formula difference between (PO4)6(OH)2 (Ca / P=1.67) and DCPD (CaHPO4·2H2O, etc., Ca / P<1.67) means that the metastable crystalline phase transformation into hydroxyapatite is inevitably accompanied by the formation of other impurity crystalline phases, resulting in limited purity improvement. Furthermore, this method is energy-intensive (generally, transformation to hydroxyapatite requires temperatures above 400℃). Therefore, a method that can simultaneously achieve purification, drying, and energy saving is currently lacking. Summary of the Invention

[0005] This invention discloses a method for preparing high-purity hydroxyapatite dry powder, which solves the technical problems in the prior art.

[0006] This application provides a method for preparing high-purity hydroxyapatite dry powder, comprising: mixing a calcium salt solution and a phosphate solution to form a mixed liquid; reacting and washing the mixed liquid in a reactor to obtain a hydroxyapatite precursor containing impurity crystalline phases; mixing the hydroxyapatite precursor containing impurity crystalline phases with water to form a precursor solution; grinding and dispersing the precursor solution in a ball mill to form a slurry; crushing and drying the slurry under the action of a high-pressure airflow in a spray dryer to form hydroxyapatite particles and impurity crystalline phase particles; agglomerating the hydroxyapatite particles and impurity crystalline phase particles during the falling process to form hydroxyapatite agglomerates and impurity crystalline phase agglomerates; and separating the hydroxyapatite agglomerates and impurity crystalline phase agglomerates due to their different particle sizes, thereby obtaining high-purity hydroxyapatite dry powder.

[0007] In one possible implementation, the slurry feed rate is 1-20 mL / min, the inlet air temperature of the spray dryer is 100-200℃, the inlet air rate of the spray dryer is 100-2000 L / min, and the high-pressure airflow pressure of the spray dryer is 0.1-0.3 MPa.

[0008] In one possible implementation, the concentration of hydroxyapatite containing the impurity crystalline phase in the precursor solution is 10-30 wt%. In one possible implementation, the precursor solution is further provided with an additive, which is at least one of polyvinyl alcohol, polyethylene glycol, polyacrylamide, sodium polyacrylate, sodium alginate, carboxymethyl cellulose, and hyaluronic acid, and the concentration of the additive in the precursor solution is 1-5 wt%.

[0009] In one possible implementation, the concentration of the additives in the slurry is 1-2 wt%.

[0010] In one possible implementation, the precursor solution is ball-milled in a ball mill for 10-20 minutes at a speed of 50-150 rpm.

[0011] In one possible implementation, the hydroxyapatite particles in the precursor solution have a particle size of less than 5 μm; the hydroxyapatite agglomerates have a particle size of 1-30 μm; and the impurity crystalline agglomerates have a particle size of 10-100 μm.

[0012] In one possible implementation, the calcium salt includes at least one of calcium nitrate, calcium chloride, and calcium hydroxide; the phosphate includes at least one of diammonium hydrogen phosphate, ammonium hydrogen phosphate, and sodium phosphate.

[0013] In one possible implementation, the calcium-to-phosphorus molar ratio is 1.67.

[0014] In one possible implementation, the reaction temperature is 15-40°C, the pH value of the reaction is 4-11, and the reaction time is 1-4 hours.

[0015] The technical solution adopted in this invention can achieve the following beneficial effects: This invention provides a method for preparing high-purity hydroxyapatite dry powder. The method involves mixing a hydroxyapatite precursor containing impurity crystalline phases with water to form a precursor solution. The precursor solution is then ground and dispersed in a ball mill to form a slurry. The dispersed slurry is then placed in a spray dryer, where it is crushed and dried under high-pressure airflow to form hydroxyapatite particles and impurity crystalline phase particles. During descent, the hydroxyapatite particles and impurity crystalline phase particles agglomerate to form hydroxyapatite aggregates and impurity crystalline phase aggregates of different particle sizes. Due to the difference in particle size, the hydroxyapatite aggregates and impurity crystalline phase aggregates separate, thus obtaining high-purity hydroxyapatite dry powder with virtually no impurity crystalline phases. This preparation method removes impurity crystalline phases and dries the product without altering the crystal structure, resulting in high-purity hydroxyapatite dry powder that is easy to store and use. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below, which constitute a part of the present invention. The illustrative embodiments of the present invention and their descriptions explain the present invention and do not constitute an improper limitation of the present invention.

[0017] In the attached diagram: Figure 1 The image shows X-ray diffraction patterns of hydroxyapatite dry powder from comparative examples and Examples 1-2 of the present invention. Figure 2 The image shown is a 300x SEM image of the product collected in the cyclone separator of Embodiment 1 of the present invention. Figure 3 The image shown is a scanning electron microscope (SEM) image (5000x) of the product collected in the cyclone separator of Embodiment 1 of the present invention. Figure 4 The image shown is a 300x SEM image of the product collected in the cyclone separator of Embodiment 2 of the present invention. Figure 5 The image shown is a light micrograph of the product from the drying chamber in Example 2 of the present invention (scale bar is 20 μm). Figure 6 The image shown is a light microscope image (scale bar is 20 μm) of the product collected in the collection bottle below the drying chamber in Example 2 of the present invention. Figure 7The image shown is a light microscope image of the product inside the cyclone separator in Embodiment 2 of the present invention (scale bar is 20 μm). Figure 8 The image shown is a light microscope image (scale bar is 200 μm) of the product collected in the collection bottle below the cyclone separator in Embodiment 2 of the present invention. Figure 9 The image shown is a light microscope image (scale bar is 20 μm) of the product collected in the cyclone separator in Example 3 of the present invention. Figure 10 The image shown is a light microscope image (scale bar is 200 μm) of the product collected in the cyclone separator in Example 3 of the present invention. Figure 11 The image shown is a 300x SEM image of the hydroxyapatite dry powder of the comparative example of the present invention. Figure 12 The image shown is a scanning electron microscope (SEM) image (5000x) of the hydroxyapatite dry powder of the comparative example of the present invention. Detailed Implementation

[0018] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0019] Example 1 (1) Mix calcium nitrate solution and diammonium hydrogen phosphate solution in a calcium-to-phosphorus molar ratio of 1.67 to form a mixture. Place the mixture in a reactor and react for 2 hours at a temperature of 30°C and a pH of 8 to form a precipitate. Wash the precipitate with deionized water or ethanol to obtain a hydroxyapatite precursor containing impurity crystal phases.

[0020] (2) A precursor solution is formed by mixing a hydroxyapatite precursor containing impurity crystal phases with water. The concentration of hydroxyapatite in the precursor solution is 20wt%. The hydroxyapatite particles in the precursor solution are plate-like structures with a particle size of less than 5μm. The precursor solution is placed in a ball mill (model F-T4) and ground and dispersed into a slurry under low speed conditions. The grinding time is 15min and the ball mill speed is 100rpm. The particle size of hydroxyapatite remains unchanged during the grinding process. Then the slurry is placed in the feed chamber of a spray dryer (model YC-510) for spray drying. The feed rate of the slurry is 5ml / min, the inlet temperature is 110℃, the inlet air rate is 750mL / min, and the pressure of the high-pressure airflow is 0.15MPa.

[0021] The feed chamber is located at the top of the drying chamber, while the hot air and high-pressure airflow inlets are located on the sides. When the spray dryer is turned on, the slurry falls from the top of the drying chamber, and the high-pressure airflow and hot air blow out from the sides. The slurry is broken into small droplets by the high-pressure airflow, consisting of hydroxyapatite particles and impurity crystalline particles. These droplets absorb heat from the hot air, and the water or solvent in the droplets evaporates. At this point, the hot air contains both hydroxyapatite particles and impurity crystalline particles. During their descent, these particles agglomerate to form hydroxyapatite agglomerates and impurity crystalline agglomerates of different sizes. Hydroxyapatite particles smaller than 5 μm agglomerate to form hydroxyapatite agglomerates with a diameter of 1-30 μm, which are nearly spherical in shape. The agglomerated impurity crystalline agglomerates have a diameter of 10-100 μm and are plate-like in shape. The particle size of the aggregates is generally larger than that of the hydroxyapatite agglomerates. Under the action of gravity, the impurity crystalline agglomerates detach from the hot air in advance and fall into the inner wall of the drying chamber or the collection bottle below the drying chamber. At the same time, the hot air blows the hydroxyapatite agglomerates into the cyclone separator or into the collection bottle below the cyclone separator. In addition, for hydroxyapatite agglomerates with a particle size between 10-30μm and impurity crystalline agglomerates with a similar particle size, due to their different shapes, the plate-shaped impurity crystalline agglomerates have a larger contact area with the inner wall of the drying chamber, and are thus adsorbed and fixed on the inner wall of the drying chamber. The spherical hydroxyapatite agglomerates have a small contact area with the inner wall of the dryer and are not easily adsorbed on the inner wall of the drying chamber. Under the action of hot air, the hydroxyapatite agglomerates are blown into the cyclone separator or fall into the collection bottle below the cyclone separator, thus obtaining high-purity hydroxyapatite dry powder.

[0022] The collected hydroxyapatite powder was subjected to X-ray diffraction and scanning electron microscopy (SEM). Figure 1 The image shows the X-ray diffraction patterns of the hydroxyapatite dry powder of the comparative examples and Examples 1-2 of this invention. The characteristic peak of calcium hydrogen phosphate dihydrate (DCPD) is around 10°, and the characteristic peak of hydroxyapatite (HAp) is around 31°. Figure 1 As shown, the X-ray diffraction pattern of hydroxyapatite in Example 1 does not show obvious characteristic peaks of calcium hydrogen phosphate dihydrate (DCPD), which indicates that the hydroxyapatite dry powder prepared in this example contains almost no impurities. Figure 2 The image shown is a 300x SEM image of the product collected in the collection bottle under the cyclone separator in Embodiment 1 of the present invention; Figure 2 As shown in the figure, most of the aggregates are spherical hydroxyapatite aggregates of 10-20 μm, with almost no platy impurity crystal aggregates. Figure 3 The image shown is a scanning electron microscope (SEM) image (5000x) of the product collected in the cyclone separator of Embodiment 1 of the present invention. Figure 3It is a hydroxyapatite aggregate obtained by agglomeration of multiple plate-like structures with a particle size of less than 5 μm.

[0023] Example 2 (1) Mix calcium chloride solution and ammonium hydrogen phosphate solution in a calcium-to-phosphorus molar ratio of 1.67 to form a mixture. Place the mixture in a reactor and react for 2 hours at a temperature of 30°C and a pH of 8 to form a precipitate. Wash the precipitate with deionized water or ethanol to obtain a hydroxyapatite precursor containing impurity crystal phases.

[0024] (2) A precursor solution was prepared by mixing hydroxyapatite precursor containing impurity crystalline phases, water, and polyvinyl alcohol. The concentration of hydroxyapatite in the precursor solution was 10 wt%, the concentration of polyvinyl alcohol was 1 wt%, and the hydroxyapatite particles in the precursor solution had a plate-like structure with a particle size of less than 5 μm. The precursor solution was placed in a ball mill (model F-T4) and ground and dispersed into a slurry under low speed conditions. The grinding time was 15 min, the ball mill speed was 100 rpm, and the particle size of hydroxyapatite remained unchanged during the grinding process. Then, the slurry was placed in the feed chamber of a spray dryer (model YC-510) for spray drying. The slurry feed rate was 5 ml / min, the inlet air temperature was 110℃, the inlet air rate was 750 mL / min, and the atomization pressure was 0.15 MPa.

[0025] The feeding chamber is located at the top of the drying chamber, while the hot air and high-pressure airflow inlets are located on the sides of the drying chamber. When the spray dryer is turned on, the slurry falls from the top of the drying chamber, and the high-pressure airflow and hot air blow from the sides of the drying chamber. The slurry is broken into small droplets by the high-pressure airflow, namely hydroxyapatite particles and impurity crystalline particles. The small droplets absorb heat from the hot air, and the moisture and solvent are evaporated. At this time, there are two types of particles in the hot air: hydroxyapatite particles and impurity crystalline particles. During the descent, the hydroxyapatite particles and impurity crystalline particles agglomerate to form hydroxyapatite agglomerates and impurity crystalline agglomerates of different particle sizes. Under the action of gravity and the adsorption force of the inner wall of the drying chamber, the impurity crystalline agglomerates detach from the hot air in advance and fall into the inner wall of the drying chamber or into the collection bottle below the drying chamber. Under the action of the hot air, the hydroxyapatite agglomerates are blown into the cyclone separator or fall into the collection bottle below the cyclone separator, thereby obtaining high-purity hydroxyapatite dry powder.

[0026] The collected hydroxyapatite powder was subjected to X-ray diffraction and scanning electron microscopy (SEM). Figure 1 The image shows the X-ray diffraction patterns of hydroxyapatite dry powder from comparative examples and Examples 1-2 of this invention. The characteristic peak of calcium hydrogen phosphate dihydrate (DCPD) is around 10°, and the characteristic peak of hydroxyapatite (HAp) is around 31°. Figure 1It can be seen that the X-ray diffraction pattern of the hydroxyapatite dry powder in Example 2 does not contain the characteristic peak of calcium hydrogen phosphate dihydrate (DCPD), which indicates that there are almost no impurity crystalline phases in the hydroxyapatite dry powder of Example 2. Figure 4 The image shown is a 300x SEM image of the product collected in the cyclone separator of Embodiment 2 of the present invention. Figure 4 Most of the aggregates are 10-20 μm hydroxyapatite agglomerates, with almost no platy impurity crystal agglomerates.

[0027] Figure 5 The image shown is a light micrograph of the product from the drying chamber in Example 2 of the present invention (scale bar is 20 μm). Figure 5 The presence of numerous flaky impurity crystalline aggregates in the drying chamber was observed. Figure 6 The image shown is a light micrograph (scale bar 20 μm) of the product in the collection bottle below the drying chamber in Embodiment 2 of the present invention. A large number of flaky impurity crystal phase aggregates and a very small number of spherical hydroxyapatite aggregates are present in the collection bottle below the drying chamber. This indicates that the impurity crystal phases are adsorbed on the inner wall of the drying chamber or collected in the collection bottle below the drying chamber.

[0028] Figure 7 The image shown is a light microscope image (scale bar is 20 μm) of the product inside the cyclone separator in Embodiment 2 of the present invention. Figure 7 The aggregates are mostly spherical hydroxyapatite, with almost no platy aggregates. Figure 8 The image shown is a light microscope image (scale bar is 200 μm) of the product collected in the collection bottle below the cyclone separator in Embodiment 2 of the present invention. Figure 8 The hydroxyapatite aggregates are primarily spherical, with almost no platy aggregates. Compared to the spherical aggregates, the platy impurity crystalline aggregates have a larger contact area with the inner wall of the drying chamber, thus adsorbing and fixing them to the inner wall. Furthermore, because the impurity crystalline aggregates are larger than the hydroxyapatite aggregates, they fall into the collection bottle below the dryer under gravity. The hydroxyapatite aggregates, being spherical, have a smaller contact area with the dryer's inner wall and are relatively smaller in size, making them easily carried by hot air into the cyclone separator or falling into the collection bottle below the cyclone separator. After collection, high-purity hydroxyapatite powder is obtained.

[0029] Example 3 The implementation method of Example 3 is the same as that of Example 2, except that: A precursor solution was prepared by mixing hydroxyapatite precursor containing impurity crystalline phases, water, polyvinyl alcohol, and polyethylene glycol. The concentration of hydroxyapatite in the precursor solution was 10 wt%, the concentration of polyvinyl alcohol in the precursor solution was 1 wt%, and the concentration of polyethylene glycol in the precursor solution was 1 wt%.

[0030] The hydroxyapatite powder in the collection bottle below the cyclone separator of the spray dryer was observed under an optical microscope. Figure 9 The image shown is a light microscope image (scale bar 20 μm) of the product collected in the cyclone separator in Embodiment 3 of the present invention. Figure 9 The main body consists of spherical hydroxyapatite aggregates. Figure 10 The image shown is a light microscope image (scale bar 200 μm) of the product collected in the collection bottle under the cyclone separator in Example 3 of the present invention; as shown Figure 10 As shown, under a low-power microscope, Figure 10 The hydroxyapatite aggregates are mostly nearly spherical, indicating that adding the two additives can still yield hydroxyapatite powder with high purity.

[0031] Example 4 The implementation method of Example 4 is the same as that of Example 1, except that: A precursor solution was prepared by mixing a hydroxyapatite precursor containing impurity crystalline phases with water. The concentration of hydroxyapatite containing impurity crystalline phases in the precursor solution was 30 wt%. The particle size of the hydroxyapatite particles in the precursor solution was less than 5 μm.

[0032] Even when the concentration of hydroxyapatite containing impurity crystalline phases in the current precursor solution is 30 wt%, high-purity hydroxyapatite dry powder can still be prepared by the method in Example 4.

[0033] Example 5 The implementation method of Example 5 is the same as that of Example 1, except that: Calcium hydroxide solution and sodium phosphate solution were mixed in a calcium-to-phosphorus molar ratio of 1.67 to form a mixture. The mixture was placed in a reactor and reacted for 2 hours at 30°C and pH 8 to form a precipitate. The precipitate was washed with deionized water or ethanol to obtain a hydroxyapatite precursor containing impurity crystalline phases.

[0034] When the raw materials calcium hydroxide solution and sodium phosphate solution are selected for precipitation reaction, and the concentration of hydroxyapatite containing impurity crystalline phase in the prepared precursor solution is 20wt%, high-purity hydroxyapatite dry powder can still be prepared by the method of Example 5.

[0035] Example 6 The implementation method of Example 6 is the same as that of Example 1, except that: The slurry was placed in the feed chamber of a spray dryer (model YC-510) for spray drying. When the slurry feed rate was 1 ml / min, the inlet air temperature was 100℃, the inlet air rate was 100 mL / min, and the pressure of the high-pressure airflow was 0.1 MPa, high-purity hydroxyapatite dry powder could still be prepared by the method in Example 6.

[0036] Example 7 The implementation method of Example 7 is the same as that of Example 1, except that: The slurry was placed in the feed chamber of a spray dryer (model YC-510) for spray drying. When the slurry feed rate was 20 ml / min, the air inlet temperature was 200℃, the air inlet rate was 2000 mL / min, and the pressure of the high-pressure airflow was 0.3 MPa, high-purity hydroxyapatite dry powder could still be prepared by the method in Example 7.

[0037] Comparative Example (1) Calcium nitrate solution and diammonium hydrogen phosphate solution are mixed in a calcium-to-phosphorus molar ratio of 1.67 to form a mixture. The mixture is placed in a reactor and reacted for 2 hours at a temperature of 30°C and a pH of 8 to form a precipitate. The precipitate is washed with deionized water or ethanol to obtain a hydroxyapatite precursor containing impurity crystal phases.

[0038] (2) Vacuum drying and sintering of hydroxyapatite A precursor solution containing impurity crystalline phases of hydroxyapatite was prepared by mixing it with water. The concentration of hydroxyapatite containing impurity crystalline phases in the precursor solution was 10 wt%. The precursor solution was dispersed into a slurry in a ball mill (model F-T4) for 15 min at a speed of 100 rpm. The slurry was then dried in a vacuum dryer at 70°C for 1 day. After drying, the sintered hydroxyapatite powder was sintered at 600°C. X-ray diffraction and scanning electron microscopy of the obtained hydroxyapatite powder revealed that it contained a large amount of flake-like DCPD.

[0039] Figure 1 The image shows the X-ray diffraction patterns of the hydroxyapatite dry powders from Examples 1-3 of this invention. The characteristic peak of calcium hydrogen phosphate dihydrate (DCPD) is around 10°, and the characteristic peak of hydroxyapatite (HAp) is around 31°. Figure 1 As shown, the hydroxyapatite dry powder produced by the comparative method contains the impurity DCPD.

[0040] The surface morphology of hydroxyapatite dry powder was further observed by SEM scanning electron microscopy. Figure 11 The image shown is a 300x SEM image of the hydroxyapatite dry powder of the present invention as a comparative example. Figure 11 The medium contains both flaky and spherical particles. The flaky particles are calcium phosphate dihydrate (DCPD), and the remaining particles are hydroxyapatite. Figure 12 The image shown is a 5000x SEM image of the hydroxyapatite dry powder of the comparative example of the present invention. Figure 12The flaky particles are calcium hydrogen phosphate dihydrate (DCPD), and the remaining particles are hydroxyapatite. Therefore, it is evident that the hydroxyapatite dry powder produced by the comparative method contains the impurity DCPD.

[0041] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications or equivalent substitutions made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing high-purity hydroxyapatite dry powder, characterized in that, include: A calcium salt solution and a phosphate solution are mixed to form a mixture. The mixture is then placed in a reactor for reaction and washing to obtain a hydroxyapatite precursor containing impurity crystalline phases. A precursor solution is formed by mixing a hydroxyapatite precursor containing impurity crystalline phases with water. The precursor solution is placed in a ball mill for grinding and dispersion to form a slurry. Under the action of high-pressure airflow in a spray dryer, the slurry is crushed and dried to form hydroxyapatite particles and impurity crystalline phase particles. During the descent process, the hydroxyapatite particles and impurity crystalline phase particles agglomerate to form hydroxyapatite agglomerates and impurity crystalline phase agglomerates of different particle sizes. Due to the difference in particle size, the hydroxyapatite agglomerates and impurity crystalline phase agglomerates separate, thereby obtaining high-purity hydroxyapatite dry powder.

2. The preparation method according to claim 1, characterized in that, The slurry feed rate is 1-20 mL / min, the inlet air temperature of the spray dryer is 100-200℃, the inlet air rate of the spray dryer is 100-2000 L / min, and the high-pressure airflow pressure of the spray dryer is 0.1-0.3 MPa.

3. The preparation method according to claim 1, characterized in that, The concentration of hydroxyapatite containing impurity crystalline phases in the precursor solution is 10-30 wt%.

4. The preparation method according to claim 1, characterized in that, The precursor solution also contains an auxiliary agent, which is at least one of polyvinyl alcohol, polyethylene glycol, polyacryl alcohol, sodium polyacrylate, sodium alginate, carboxymethyl cellulose, and hyaluronic acid, and the concentration of the auxiliary agent is 1-5 wt%.

5. The preparation method according to claim 4, characterized in that, The concentration of the auxiliary agent is 1-2 wt%.

6. The preparation method according to claim 1, characterized in that, The precursor solution is ball-milled in a ball mill for 10-20 minutes at a speed of 50-150 rpm.

7. The preparation method according to claim 1, characterized in that, The precursor solution contains hydroxyapatite particles with a particle size of less than 5 μm; the hydroxyapatite aggregates have a particle size of 1-30 μm; and the impurity crystalline aggregates have a particle size of 10-100 μm.

8. The preparation method according to claim 1, characterized in that, The calcium salt includes at least one of calcium nitrate, calcium chloride, and calcium hydroxide; the phosphate includes at least one of diammonium hydrogen phosphate, ammonium hydrogen phosphate, and sodium phosphate.

9. The preparation method according to claim 1, characterized in that, The molar ratio of calcium to phosphorus in the mixture is 1.

67.

10. The preparation method according to claim 1, characterized in that, The reaction temperature is 15-40℃, the pH value of the reaction is 4-11, and the reaction time is 1-4 hours.